Cold rotary swaging of a tungsten heavy alloy: Numerical and experimental investigations - Kocich, Radim; Kunčická, Lenka; Dohnalík, Daniel; Macháčková, Adéla; Šofer, Michal (International journal of refractory metals & hard materials, 2016)
A finite element analysis was performed to predict behaviour of sintered tungsten-based heavy alloy during cold rotary swaging, while experimental investigations evaluated mechanical and structure properties in both, sintered and swaged material states. The simulation involved prediction of swaging force, which was subsequently compared with force measured experimentally using own designed force detection system, although other parameters, such as strain, strain rate, stress and temperature were also predicted and subsequently compared to experimental data. The results showed significant hardening and strengthening after swaging; the average ultimate strengths after sintering and swaging, respectively, were 860MPa and 1680MPa. This also contributed to very high swaging force of almost 600kN. The distribution of microhardness across the cross-section confirmed the predicted strain distribution. Texture analyses revealed a notion of cube texture given primarily by the fcc matrix in the sintered state, while several ideal orientations for both the fcc and bcc phases were observed after swaging. As indicated by grains misorientations analyses, swaging introduced residual stress, the distribution of which was in conformity with the predicted stress and strain distributions. [Display omitted] •Sintered tungsten-based heavy alloy was swaged under cold conditions.•Ultimate tensile strength almost doubled after processing (~1700MPa).•Numerically predicted swaging force confirmed by experimental dynamic force record•Predicted strain and strain rate distributions confirmed by mechanical properties•Grains misorientations indicated residual stresses, as predicted